LEARNING ISLAMIC EDUCATION MATERIAL WITH INSIGHTS MULTICULTURAL - Nursyirwan Nursyirwan; Zulkarnain Dali; Abdul Aziz Bin Mustamin (Pascasarjana s-3 IAIN Bengkulu, 2021)
Biodiversity and flora in this country is a reflection of the variety and variety of natural potentials which in turn also reflect the multicultural potential of each region, ethnicity, custom, language, geography, and many more. Then coupled with the current digital era or what is called the era of disruption, the problem of social conflict that was in the realm of its initial reality, until now has also shifted to the virtual world (both social media, internet and so on). Therefore, Islamic religious education which is identical with religious dogma should also include the multicultural values of the digital era so that people who are dialogical, inclusive, democratic, pluralist, and multiculturalist are born. The purpose of this study is to obtain an acceptable formulation of Islamic religious education learning in a multicultural perspective in the era of the industrial revolution 4.0 or digital era. The research method used in this research is a qualitative research method with a grounded theory approach. Further analysis was carried out using qualitative data analysis by John W. Creswell. The research results and conclusions state that the concept of learning Islamic religious education has a multicultural perspective in the digital era, both from the aspects of educators, students, teaching materials, strategies and methods, evaluation, and learning media must prioritize dialogical, inclusive, democratic, pluralist, and multiculturalist principles.